Skrining Bakteri Lipolitik dari Tanah Pemakaman - Mandiri, Listy Hasti; Rahayu, Triastuti; Tyastuti, Erma Musbita; Sidiq, Yasir (Universitas Muhammadiyah Prof. Dr. Hamka, 2023)
Background: The cemetery is an area for the burial of corpses so that active decomposition of bodies occurs. One of the decomposition bacteria that might be found is lipolytic bacteria because the human body comprises 21,33-32,51 % lipids. Explorations of lipolytic bacteria from cemeteries in Indonesia have not been found, so this research needs to be done. This non-experimental study aimed to select and identify lipolytic bacterial isolates from the Pracimaloyo cemetery, Surakarta. Method: A total of 36 bacterial isolates were selected for their lipolytic activity using tributyrin media. The lipolytic index determines lipolytic activity. Identification of lipolytic bacteria based on colonial morphology and Gram staining. Result: The study showed that 22.2% (8 isolates) showed a lipolytic positive, with the largest lipolytic index (LI) value of 2.5 (isolate P36). Bacterial colonies are circular-shaped, have entire edges, flat elevation, and are yellow or white. Gram staining results showed that the isolated is a group of Gram-negative bacteria in the form of coccus. Conclusion: The conclusion of this study suggests that bacterial isolates from Pracimaloyo cemetery that have potential lipolytic activity, which is likely to be from the genera Pseudomonas and Klebsiella, were obtained.